2016
DOI: 10.1149/07215.0001ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Long Term Stability of Antimony Sulfide-Based Hybrid Solar Cells

Abstract: Sb2S3-based hybrid solar cells with electron transporting layer of TiO2 or ZnO nanoparticles in addition to poly(3-hexylthiophene)-2,5-diyl / (3, 4-ethylenedioxythiophene) : poly(styrene sulfonate), zinc phthalocyanine (ZnPc), or MoO3 for hole transporting layer were prepared and compared their photovoltaic properties with or without encapsulation by using glass and UV cut-off film. Among these hybrid solar cells, it was found that a combination of glass-ITO/TiO2/Sb2S3/ZnPC/Au encapsulated with glass and UV cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Based on the above statement, more inorganic compound semiconductors are being developed, such as MoO 3 , V 2 O 5 , and nickel oxide (NiO x ). [10][11][12] Among these commonly used inorganic hole transport layers, NiO x has attracted great interest due to its wide bandgap, high optical transmittance, good chemical stability, low-temperature preparation feasibility, and the low production cost. [13][14][15][16] It can be prepared by sol-gel method, [17] spray pyrolysis, [18] atomic layer deposition, [19] and magnetron sputtering [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above statement, more inorganic compound semiconductors are being developed, such as MoO 3 , V 2 O 5 , and nickel oxide (NiO x ). [10][11][12] Among these commonly used inorganic hole transport layers, NiO x has attracted great interest due to its wide bandgap, high optical transmittance, good chemical stability, low-temperature preparation feasibility, and the low production cost. [13][14][15][16] It can be prepared by sol-gel method, [17] spray pyrolysis, [18] atomic layer deposition, [19] and magnetron sputtering [20] .…”
Section: Introductionmentioning
confidence: 99%
“…We also have prepared Sb2S3-based solar cells with TiO2 or ZnO nanoparticles for electron transporting materials in addition to P3HT/ (3, 4-ethylenedioxythiophene) : poly(styrene sulfonate) (PEDOT : PSS), zinc phthalocyanine (ZnPc), or MoO3 as HTM and compared their photovoltaic performance. Among these hybrid solar cells, it was found that the combination with ZnPc and TiO2 has the highest durability with keeping the relative PCE of 90% after the stability test under 1 sun at 63 °C at a relative humidity of 50% for 1,500 h (14,15). Recently, HTM-free planar TiO2/Sb2S3 thin film device structure has also been reported and resulted in long durability for six months under an ambient condition (16).…”
Section: Introductionmentioning
confidence: 99%